Is there gender inequality in the impacts of energy poverty on health? - Zhang, Ziyu; Linghu, Yuting; Meng, Xue; Yi, Hong (Frontiers in Public Health, 2022)
This paper aims to study the gender inequality in the health impacts of energy poverty. Using the Chinese Family Panel Studies (CFPS) 2018 data, we examine the gender heterogeneous effects of energy poverty on residents' health. The empirical results indicate that energy poverty would increase the ratio of respiratory disease, hospitalization as well as the healthcare expenditure. The effects are moderated by housework time. Moreover, we explore the gender inequality of the health impacts and find that women's health is more severely impaired and the effect of gender inequality is heterogeneous between urban and rural areas. We further investigate the historical origins of intra-household division of labor and reveal that the root of gender inequality in the health effects of energy poverty is status inequality. The government should give the first priority to energy poverty alleviation through modern energy network construction. Providing the energy-deprived families with ventilation equipment and medical insurance should be considered as the next step. Finally, it is imperative to eradicate urban-rural dual structure and legislate to ensure gender equality in the whole society.